Dictatorial domains in preference aggregation - Ozdemir, Ugur; Sanver, M. Remzi (Springer, 2007)
We call a domain of preference orderings dictatorial if there exists no Arrovian (Pareto optimal, IIA and non-dictatorial) social welfare function defined over that domain. In a finite world of alternatives where indifferences are ruled out, we identify a condition which implies the dictatoriality of a domain. This condition, to which we refer as being essentially saturated, is fairly weak. In fact, independent of the number of alternatives, there exists an essentially saturated ( hence dictatorial) domain which consists of precisely six orderings. Moreover, this domain exhibits the superdictatoriality property, i.e., every superdomain of it is also dictatorial. Thus, given m alternatives, the ratio of the size of a superdictatorial domain to the size of the full domain may be as small as 6/m!, converging to zero as m increases.
Keywords: Social-Welfare Functions; Voting Procedures; Majority-Rule; Strategy; Existence; Theorems; Private